Hydrodechlorination of 4-chloro-2-aminophenol into a recyclable product using Ni- and Cu-based catalysts - Shetty, Rohit R.; Raut, Sandesh S.; Kulkarni, Prashant S.; Kamble, Sanjay P. (Industrial & Engineering Chemistry Research, 2022)
The 4-chloro-2-amino phenol (4C2AP) bearing wastewater is produced while manufacturing dyes and pharma-ceutical ingredients. Ni-and Cu-based cost-effective catalysts were developed, typically characterized, and subjected to hydrodechlori-nation (HDC) of 4C2AP. The role of reducing agents, concentration, pH of wastewater, presence of salt, reaction temperature, catalyst reuse, and the kinetics was investigated. A selective makeover of 2-amino phenol (2AP) was analyzed by HPLC, LCMS, and NMR. A complete HDC of 4C2AP with remarkable selectivity (98%) toward 2AP was achieved using a Ni0 catalyst and NaBH4 at room temperature. It is observed that the alkaline condition, the presence of salt, and a high reaction temperature favor the HDC process. A maximum of 1 g L-1 of the Ni0 loading is found to be sufficient to dechlorinate the pollutant. It can be concluded that the catalytic HDC is a technically viable and inexpensive process for the conversion of 4C2AP into a valuable product, 2AP.